Analisis Keterlaksanaan Pembelajaran Berdiferensiasi di Kelas XII MIPA Sekolah X - Lauri Olsa (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to analyze the implementation of differentiated learning in class XII MIPA School X which still uses the 2013 Curriculum, and to identify the obstacles and challenges faced in its implementation. Differentiated learning, which is designed to accommodate the diversity of students' abilities and learning styles, has not been fully implemented in the school. The method used in this study is qualitative with a case study design, involving observation, interviews with teachers and students, and analysis of related documents. The results of the study indicate that although teachers are aware of the importance of differentiated learning, its implementation is constrained by time constraints, teachers' in-depth understanding, and difficulties in compiling materials and assessments that are appropriate to the diverse needs of students. In addition, limited resources and lack of technological support are also obstacles to the implementation of differentiated learning. Based on these findings, the study recommends that schools provide further training to teachers, prepare more flexible Learning Implementation Plans (RPP), and utilize technology to support more personal and inclusive learning. With these steps, it is expected that differentiated learning can be implemented more effectively in class XII MIPA of School X.